Pyrethroid-linked resistance allelic mutations by molecular analysis in wild human head louse (Phthiraptera: Pediculidae) populations from schoolgirls of South Iran. (August 2022) - Mohammadi, J.; Alipour, H.; Azizi, K.; Shahriari-Namadi, M.; Kalantari, M.; Ebrahimi, S.; Moemenbellah-Fard, M.D.
Abstract: Background: Human head louse, Pediculus humanus capitis De Geer, 1767 (Anoplura: Pediculidae), is one of the most frequent ectoparasites infesting Homo sapiens worldwide. Reduced sensitivity to treatment due to genetic mutations, in particular knockdown resistance ( kdr ) (or target site insensitivity) allele, has led to this infestation prevalence. Molecular characterization of this resistance has a crucial impact on selecting appropriate treatment protocol. The aim of this study was to investigate kdr gene mutations on voltage-sensitive sodium channel (VSSC) among wild head lice samples from Fars province, southern Iran. Methods: Head lice were collected using plastic detection combs on girls enrolled in public schools from 10 counties in Fars province. The specimens were screened in 10 pools (each pool per county containing 35 specimens), with three pools (30%) being positive. Following species identification with valid entomological keys, 350 (68%) out of 514 randomly collected adult head lice were analyzed after their somatic genomic DNA extraction using Sinaclon kit. Samples were investigated by polymerase chain reactions (PCR), and the amplicon was subsequently sequenced. Results: Sequence analysis showed that the sodium channel genes in the pooled ectoparasites had two intron and three exon regions. Single (L840F), double (I836L, E837K), and triple novel point mutations (V875L, Q876P, S879V); the last involving two concomitant allelic substitutions; were discovered in the second and third exon regions of head louse DNA on chromosome II from three (30%) counties. Other exon or intron regions remained non-mutated from the remaining seven counties. Conclusions: The detection of six amino acid substitutions from 30% of examined head lice among infested schoolgirls reveal that mutants are minutely developing. These findings provide further incentive to recapitulate the legitimacy of current control measures and resolve dynamics of resistance in human head louse populations.